Peningkatan Kinerja Karyawan Hotel Berbasis Talent Management - Mozes Tomasila; Godprit Haris Touwely (Journal of Business Application, 2022)
One of the strategies that can be used in creating qualified human resources in terms of performance, ethics, or abilities and skills is the application of Talent Management. In this context, companies can run training on Talent training. This research is intended to conduct a study on "Improvement of Hotel Employee Performance in Ambon City Based on Talent Management Case Studies at the Golden Palace Hotel." It is suspected that training has a positive impact on employee performance. ) is 14,171 while at a = 5% and df = 33 the t table value is = 1.504. Because t_count > t_table, it is partially proven that employee training variables have a significant effect on the performance of employees at the Golden Palace Hotel, Ambon City. Keywords: Talent Management, Training, and Performance